PELAKSANAAN PROJEK SUMBANG DUO BALEH PADA DIMENSI BERIMAN, BERTAKWA KEPADA TUHAN YANG MAHA ESA, DAN BERAKHLAK MULIA DI MTsN 2 KOTA PARIAMAN - Annisa Indriani; Khadijah; Rilci Kurnia Illahi; Duski Samad; Aziza Meria (CV. ADIBA AISHA AMIRA, 2025)
This thesis was motivated by the discovery of impolite behavior among students, such as not greeting teachers when passing by them, as well as many students eating and drinking while walking or standing. This condition became a serious concern, considering that the madrasah was expected to instill values of politeness and other moral behaviors. In addition, the